2006
DOI: 10.1248/bpb.29.1064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2-Methoxyestradiol, Buthionine Sulfoximine and Hydrogen Peroxide on the Viability of Renal Carcinoma Cell Lines (ACHN and ACVB)

Abstract: Reactive oxygen species (ROS) are constantly generated in cells by several biological metabolic processes. A moderate level of intracellular ROS is thought to be important as a stimulant of cellular proliferation. However, the overproduction of ROS can result in detrimental cellular damage, including lipid peroxidation, DNA damage, protein oxidation and enzyme inactivation, which can ultimately lead to cell death.1,2) Aerobic cells contain several antioxidant enzymes, such as superoxide dismutase (SOD), catala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The functions of TXNDC5 and IDH1 have not been characterized in RCC and it is also possible that NR4A1 regulates other similar genes and this is currently being investigated. Since previous studies show that other ROS-inducing antineoplastic agents inhibit growth and survival of RCC [ 42 , 43 ], the induction of ROS by C-DIM/NR4A1 antagonists contributed to the anticancer activity of these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The functions of TXNDC5 and IDH1 have not been characterized in RCC and it is also possible that NR4A1 regulates other similar genes and this is currently being investigated. Since previous studies show that other ROS-inducing antineoplastic agents inhibit growth and survival of RCC [ 42 , 43 ], the induction of ROS by C-DIM/NR4A1 antagonists contributed to the anticancer activity of these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…So far, metabolites identified in this study have been reported in these three cell lines. [27][28][29] In 786-O, metabolites of glycolysis and the TCA cycle were identified. 27 Damaraju et al 28 reported that nucleoside metabolites with antitumor effects, such as glycine, increased in Caki-1.…”
Section: F I G U R Ementioning
confidence: 99%
“…27 Damaraju et al 28 reported that nucleoside metabolites with antitumor effects, such as glycine, increased in Caki-1. Additionally, Hirai et al 29 showed that the anticancer effect was related to an increase in the intracellular contents of glutaminolysis in ACHN. As cancer bioavailability was associated with intracellular concentrations of metabolites from these results, we can assume that evaluating intracellular metabolites would be helpful to understand the relationship between recurrence and urinary metabolites.…”
Section: F I G U R Ementioning
confidence: 99%